ANALISIS KEBUTUHAN SUBSIDI PERUMAHAN DI KOTA BANDA ACEH - Nanda Setianto; Amri Amri (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstract The research aims to analyze the housing subsidy needs in Banda Aceh, the model used multiple linear regression the dependent variable is the willingnest to accept and age, income, family size as independent variables, the data used are primary data totalling 99 respondents taken by purposive random sampling to nine sub districts in the city of Banda Aceh. The result show that income and family size have positive and significant impact on the desire to receive housing subsidies, but age does not significantly effect the desire to receive housing subsidies. The estimated total economic value from the desire to receive housing subsidies is IDR 7.451.743.000 and on average, the desire to receive housing subsidies is around IDR 75.270.130. The policy implication from this research is that the amount of subsidy is relatively small and the goverment should allocate the founds to subsidies the housings for the relatively low income earners.Keywords: subsidy needs, age, income, family size, Willingnest to Accept (WTA)